Pemanfaatan Majalah Umdah Sebagai Media Pembelajaran Santri Dayah MUDI Mesjid Raya Samalanga Aceh - Subki, Tajus; Saifannur, Saifannur (Penerbit Widina, Widina Media Utama, 2022)
Learning media is very important for students in supporting their learning. Umdah magazine as one of the print media published at MUDI Mesjid Raya Samalanga can be used by students as a learning support media. So the formulation of the problem in this study is the form of the use of Umdah Magazine as a learning medium for MUDI Mesjid Raya Samalanga students and the obstacles to the use of Umdah Magazine as a learning resource for MUDI Mesjid Raya Samalanga students. This research is a type of qualitative research with a phenomenological approach. The place that became the location of the study was Dayah MUDI Mesjid Raya Samalanga which is located in Mideun Jok Village, Samalanga District, Bireuen Regency. The form of use of Umdah Magazine as a learning medium for MUDI students at the Samalanga Grand Mosque is as follows: 1) add students' insights into contemporary legal studies; 2) enriching religious science references; 3) as a medium to channel the writing potential of students; 4) understanding the world of literacy; 5) add reading material from reliable sources; 6) make it easier for students to understand the yellow book; 7) enrich the vocabulary of students in writing and conveying. The obstacles to the use of Umdah Magazine as a learning medium for MUDI Mesjid Raya Samalanga students are as follows: 1) lack of interest in reading students; 2) the late publication of Umdah Magazine because the sources of writings received by the editors were insufficient in the content of the magazine rubric; 3) Umdah magazine is considered still uninteresting for some students to read, because the discussion is too scientific so it seems monotonous; 4) the tight study schedule of students set by Dayah, so that it has an effect on the lack of time used to read Umdah Magazine as a supporting learning resource.ABSTRAKMedia pembelajaran merupakan hal yang sangat penting bagi santri dalam menunjang belajarnya. Majalah Umdah sebagai salah satu media cetak yang diterbitkan di MUDI Mesjid Raya Samalanga bisa dimanfaatkan oleh santri sebagai media penunjang pembelajaran. Maka yang menjadi rumusan masalah dalam penelitian ini adalah bentuk pemanfaatan Majalah Umdah sebagai media pembelajaran santri MUDI Mesjid Raya Samalanga dan kendala pemanfaatan Majalah Umdah sebagai sumber belajar santri MUDI Mesjid Raya Samalanga. Penelitian ini merupakan jenis penelitian kualitatif dengan pendekatan fenomenologi. Adapun tempat yang menjadi lokasi penelitian adalah Dayah MUDI Mesjid Raya Samalanga yang berlokasi di Desa Mideun Jok Kecamatan Samalanga Kabupaten Bireuen. Bentuk pemanfaatan Majalah Umdah sebagai media pembelajaran santri MUDI Mesjid Raya Samalanga adalah sebagai berikut: 1) menambah wawasan santri tentang kajian hukum kontemporer; 2) memperkaya referensi ilmu agama; 3) sebagai media untuk menyalurkan potensi menulis santri; 4) memahami dunia literasi; 5) menambah bahan bacaan dari sumber-sumber terpercaya; 6) memudahkan santri dalam memahami kitab kuning; 7) memperkaya kosa kata santri dalam menulis dan menyampaikan. Kendala pemanfaatan Majalah Umdah sebagai media pembelajaran santri MUDI Mesjid Raya Samalanga sebagai berikut: 1) kurangnya minat membaca santri; 2) terlambatnya penerbitan Majalah Umdah karena sumber tulisan yang diterima redaksi tidak mencukupi isi rubrik majalah; 3) Majalah Umdah dinilai masih kurang menarik untuk dibaca oleh sebagian santri, karena pembahasannya terlalu ilmiah sehingga terkesan monoton; 4) padatnya jadwal belajar santri yang ditetapkan dayah, sehingga berefek kepada kurangnya waktu yang digunakan untuk membaca Majalah Umdah sebagai sumber belajar penunjang.